Optimization of a Loop Mediated Isothermal Amplification (LAMP) Assay for In-Field Detection of Dichelobacter nodosus With aprV2 (VDN LAMP) in Victorian Sheep Flocks - Best, Nickala; Rawlin, Grant; Suter, Robert; Rodoni, Brendan; Beddoe, Travis (Frontiers in Veterinary Science, 2019)
Dichelobacter nodosus is the primary etiological agent of footrot in sheep and has a variety of virulence factors. Of these, AprV2, an extracellular protease, has been shown to be capable of causing severe or “virulent” disease symptoms under the right conditions. Due to this, a loop-mediated isothermal amplification (LAMP) assay for the detection of aprV2-positive D. nodosus (VDN LAMP) was developed and evaluated for field use. A sample of 19 sheep flocks (309 sheep) in Victoria, Australia, were tested to determine the optimum conditions for in-field VDN LAMP assay use and sampling, for detecting aprV2-positive D. nodosus infected sheep. VDN LAMP performance was compared to a validated rtPCR that detects aprV2 and the benign strain counterpart, aprB2, using biologically duplicate samples to determine sensitivity and specificity. Flocks were sampled either in winter-spring (moist) or early summer (dry) conditions and had a range of clinical expressions of the disease ovine footrot. Variables considered for optimizing field performance were: sample collection method, sample preparation, clinical expression of disease, and nature of the feet when sampled (moist vs. dry, clean vs. soiled). The test was found to perform best when sheep were sampled with moist, clean feet, using a dry swab with the sample prepared in alkaline polyethylene glycol, pH 13.0, as the collection buffer. A sensitivity of 89% and specificity of 97% was seen when used in-field under these conditions, when compared to aprV2 detection by rtPCR, with ‘very good’ agreement to rtPCR results. This study shows the VDN LAMP test is easy to use in-field to identify the presence of aprV2-positive D. nodosus in sheep flocks.